\(\frac{\sqrt{x}-1}{\sqrt{x}+1}-\frac{\sqrt{x}+3}{\sqrt{x}-2}-\frac{x+5}{x-\sqrt{x}-2}\) ...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 6 2021

đk: \(\hept{\begin{cases}x\ge0\\x\ne4\end{cases}}\)

\(\frac{\sqrt{x}-1}{\sqrt{x}+1}-\frac{\sqrt{x}+3}{\sqrt{x}-2}-\frac{x+5}{x-\sqrt{x}-2}\)

\(=\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}-2\right)-\left(\sqrt{x}+3\right)\left(\sqrt{x}+1\right)-x-5}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}\)

\(=\frac{x-3\sqrt{x}+2-x-4\sqrt{x}-3-x-5}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}\)

\(=\frac{-x-7\sqrt{x}-6}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-2\right)}\)

\(=\frac{\left(\sqrt{x}+1\right)\left(\sqrt{x}+6\right)}{\left(\sqrt{x}+1\right)\left(2-\sqrt{x}\right)}=\frac{\sqrt{x}+6}{2-\sqrt{x}}\)

2 tháng 9 2019

\(2,\)

\(a,\sqrt{x^2-4x+3}=3\)

\(\Rightarrow x^2-4x+3=9\)

\(\Rightarrow x^2-4x-6=0\)

\(\Rightarrow\left(x-2\right)^2=10\)

\(\Rightarrow\orbr{\begin{cases}x-2=\sqrt{10}\\x-2=-\sqrt{10}\end{cases}\Rightarrow\orbr{\begin{cases}x=2+\sqrt{10}\\x=2-\sqrt{10}\end{cases}}}\)

2 tháng 9 2019

\(a,x\ge0;x\ne1;B,x\ge0;x\ne9;C,x>0;x\ne4\)

\(d,x\ge0;x\ne25\)

29 tháng 10 2020

Trả lời nhanh giúp mình với mình cần gấp lắm